COMMUNITY BASE TREATMENT DALAM PEMBINAAN NARAPIDANA NARKOTIKA (STUDI TERHADAP PEMBINAAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN NARKOTIKA KLAS IIA YOGYAKARTA) - Haryanto Dwiatmojo (Faculty of Law, Universitas Jenderal Soedirman, 2014)
A reorientation on the execution of imprisonment as the part of criminal justice system is considerably required. It considers that most given criminal penalties stated in both Criminal Code (KUHP) and New Draft of Criminal-Procedural Code still apply imprisonment sanction. Moreover, the imprisonment imposition is aimed to protect the public as well as to rectify the offender. The further development of imprisonment imposed is perceived as a revenge. The implementation of imprisonment through correctional system is not only intended to protect the public from the dangers of crime but also to guide and give live provision of those lost people due to criminal act. However, the fact is not easy to achieve such a lofty goal since, practically, there are many obstacles and barriers encountered some of which are many kinds of violence and discrimination in prison. Key words: criminal enforcement, criminal act, prison